CULTURE TRANSFORMATION: LESSONS FROM BANK MANDIRI AND BANK BRI - Yasin, Mahmuddin (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2014)
This research aims at exploring organizational culture in state owned enterprises; Bank Mandiri and Bank BRI, and its contribution to financial performance, before and after restructuring/initial public offering (IPO). The research used qualitative approach with case study method that used coupled with exploratory and descriptive design, supported by successive approximation of technical data analysis. Eight propositions were raised from the findings regarding: (1) integration human resources planning with corporate plan, (2) skill development accommodating individual, organizational and business needs, (3) effective strategy aligned with appropriate system and proper business orientation, (4) suitable organizational structure with internal and external business environment, (5) system development oriented to customer satisfaction, (6) proper style of leadership that affects organizational culture and financial performance, (7) implementation of organizational culture in increasing corporate performance, and (8) consistency in socializing and implementing corporate culture. Keywords: state owned enterprises, organizational culture, restructuring/IPO, successive approximation, proposition.